2018
DOI: 10.1017/s1047951118000070
|View full text |Cite
|
Sign up to set email alerts
|

Gemella bergeriinfective endocarditis: a case report and brief review of literature

Abstract: Gemella is a genus of Gram-positive bacteria found in the digestive tract of humans. They rarely cause systemic illness but have been recently implicated in several serious infections. We report infective endocarditis caused by Gemella bergeri in a 23-year-old with a bicuspid aortic valve status post-intervention in infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…Different species of Aerococcus have recently been increasingly recognized as a relatively common cause of bacteremia in certain age groups and tend to cause IE [15–17]. Not within the order, but related, is the genus Gemella that can also cause IE [18].…”
mentioning
confidence: 99%
“…Different species of Aerococcus have recently been increasingly recognized as a relatively common cause of bacteremia in certain age groups and tend to cause IE [15–17]. Not within the order, but related, is the genus Gemella that can also cause IE [18].…”
mentioning
confidence: 99%
“…While no members of the genus have been detected in rodents previously, metagenomic studies show that they are common inhabitants of the oral cavity and intestinal tracts of other mammals and can be detected in wastewater [1720]. In addition, they are known to be rare causes of endogenous infection (including abscess) in humans [2126]. This isolate is phenotypically distinct from other species, while retaining the traits required for inclusion within this genus (i.e., positive Gram stain, coccus shape, lack of motility, and absence of catalase and oxidase production) [27].…”
Section: Discussionmentioning
confidence: 99%
“…G. bergeri was isolated for the first time by Collins et al in 1998 [ 3 ]. Since then to our knowledge, thirteen cases have been reported [ 4 11 ] (Table 1 ). Three of these reports did not specifically mention a clinical diagnosis and were not described in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, the susceptibility of G. bergeri was good, and the patient was therefore treated adequately. However, although intravenous ceftriaxone, gentamicin and oral rifampicin are effective antibiotics [ 4 , 6 9 , 11 ] (Table 1 ), one study showed evidence of resistance to drugs such as penicillin [ 16 ], erythromycin [ 17 ], levofloxacin and aminoglycosides [ 1 ] for Gemella. Therefore, obtaining an accurate diagnosis of Gemella using a 16S rRNA gene sequence analysis should be considered if the pathogens are not identified by Gram staining or commercial biochemical tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation